Improving Ethics and Morality in the Public Service Looking to Mexican-American Administrators / Max B. Franc. - Franc, Max B. (Distributed by ERIC Clearinghouse, 1974)
Administrative differences between the broad ethical and moral aspects of the mainstream majoritarian culture and one specific subculture--the Mexican American--are discussed. The main thesis is majoritarian inconsistency ("hyprocrisy") and the demand by the minority culture for consistency ("nonhyprocrisy"). The entire society profits from the attention being called to these discrepancies because this emphasis will be the keystone of a new ethic which will give a more useful base for models and tools for (1) identifying early signs of Watergate-types of breakdowns in the future, and (2) overcoming deleterious effects of such breakdowns. That Chicanos entering the establishmentarian processes may exhibit the same kinds of discrepancies they had initially disavowed, does not, however, detract from the validity of the insight itself. It seems that minority youth's focus on such discrepancies is associated with insecurities and frustrations in entering formerly denied mainstream public administration and governmental processes. Thus, some impacts of much-discussed subcultural variations, may be specious to extents that emerging leaders are skimmed off, in this process, with the effect that they do not remain in positions to speak for groups from which they originated. (Author/AH)